Long-Term Trends in Microseismicity During Operational Shut-Ins at the Coso Geothermal Field, California - Joanna M. Holmgren; J. Ole Kaven; Volker Oye (The Seismic Record)
Pausing injection and production can lead to induced seismicity in a variety of settings, with some of the largest events occurring during these so-called shut-ins. In geothermal fields, shut-ins are periodically conducted for the maintenance of wells and surface infrastructure, thereby offering recurring means of estimating stress changes in the subsurface that lead to increased seismicity rates. Here, we examine daily production and microseismicity data from the Coso geothermal field (CGF) in California between 1996 and 2010 to investigate the repetitive trends of operational shut-in microseismicity. Using 24 local seismic stations, we first analyze spatial and temporal trends of over 60,000 earthquakes with magnitudes between −0.4 and 3.8. We find that the northern region exhibits no significant seismicity changes during shut-ins, whereas the rest of the field experiences induced seismicity during almost every shut-in with an increasing intensity toward the southern and eastern portions of the field, possibly highlighting local differences in stress within the CGF. In addition, we cluster the seismicity using waveform cross-correlation, revealing several earthquake clusters primarily occurring during shut-in periods. These observations suggest that certain fracture and fault sections respond rapidly to changes in pore pressure and poroelastic stresses within the geothermal system, possibly highlighting main fluid pathways.